Serum Biochemistry and Histological Studies in Growing Rabbits Fed Diets Supplemented with Mucuna pruriens Leaf Meal - O. D. Oloruntola (Archives of Current Research International, 2018)
Aims: To study the serum biochemistry, hepatic and renal histology of rabbits fed diets supplemented with Mucuna leaf meal. Study Design: Completely Randomised Design. Place and Duration of Study: The experiment was carried for 12 weeks at Agricultural Technology Department Teaching and Research Farm, The Federal Polytechnic, Ado Ekiti, Nigeria. One hundred and twenty, 35-day old crossbreed (Chinchilla x New-Zealand) weaner rabbits (equal sexes; average weight 694±5 g) were randomly allotted to 4 experimental diets (30 rabbits/treatment; 3 rabbits/replicate). Methodology: A basal diet was formulated to meet the nutritional requirement of the rabbit. The basal diet was divided into 4 equal portions and designated diets 1, 2, 3 and 4. Diets 1 to 4 were supplemented with 0, 0.4, 0.8 and 1.2% Mucuna leaf meal (MLM), respectively. On day 119 of age, blood samples were collected from 10 rabbits/experimental group for serum biochemical indices determination. On the same day, the rabbit was selected from each replicate and sacrificed. The liver and kidney were surgically removed for histological studies. Results: The total protein, creatinine, and bilirubin level of the rabbits were not affected (P>0.05) by MLM supplementation. The serum cholesterol levels of the rabbits reduced (P<0.05) at 0.8% and 1.2% MLM supplementation (Diets 3 and 4). The aspartate aminotransferase concentration in rabbits fed 1.2% MLM supplemented diets significantly (P<0.05) increased compared to those fed 0% MLM supplemented the diet. The liver of rabbits fed MLM supplemented diets shows some remarkable histological alterations which vary from hepatitis, interstitial oedema (0.4% MLM supplemented diet), portal triad with congested blood vessels, mild periportal inflammation (0.8 MLM supplemented diet), and congested blood vessels of hepatic parenchyma and portal traid (1.2% MLM supplemented diets). Conclusion: Dietary MLM supplementation at 0.8% and 1.2% levels reduced the serum cholesterol concentration of the rabbits. However, dietary MLM supplementation at 1.2% level for the duration of 12 weeks caused some observable histological alteration in the liver of the rabbits.